A 360° video as visual training support for independent movement acquisition—benefit evaluation with the TAM - Rosendahl, P.; Müller, M.; Wagner, I. (German Journal of Exercise and Sport Research, 2024)
A 360° video combines the potential of conventional video technology with immersive-interactive design opportunities. The multi-perspective viewing option within a 360° video also enables possible applications as visual training support for motor learning. There are already first methodological-didactic approaches to movement learning; nevertheless, research on 360° video technology can largely be classified as exploratory. This article presents the use of 360° video as a visual training aid for the independent movement acquisition of various fascial movement exercises. In an intervention study, two randomized groups (N = 48) were used to evaluate the subjective benefit. Following the technology acceptance model, subjective benefit perception and rating of format were compared after two crossover interventions with 360° videos and/or conventional training videos. No significant differences were found for perceived usefulness (z = -1.014, p = 0.31, r = 0.105) or perceived ease of use (z = -1.278, p = 0.201, r = 0.132). The same applies for intensity of use (z = -0.247, p = 0.805, r = 0.025) and overall subjective rating (z = -1.745, p = 0.081, r = 0.18). Although no significant differences were found in the evaluation of benefits, the participants tended to use 360° videos as visual training support (M = 3.4, SD = 1.581) on a 7-point scale (1 = 360° videos). Although a generalized statement on 360° videos as visual training support is not possible due to low effect strengths, it can be stated that 360° videos are perceived at least as useful as visual training tools.